Security aware dual authentication-based routing scheme using fuzzy logic with secure data dissemination for mobile ad-hoc networks. (2018) - Borkar, Gautam M.; Mahajan, A.R.
The security of mobile ad-hoc networks (MANETs) has been getting a great deal of consideration in the field of wireless networking because MANETs are vulnerable to malicious attacks. Secure transmission without node failure in MANETs is a testing issue because of the nonappearance of centralised administration, and openness in the network topology. In order to upgrade the security of network and shield the nodes from vulnerabilities, this paper proposes a highly efficient dual authentication routing scheme which utilises fuzzy logic prediction rules to select the most reliable path and the proposed scheme coordinates with cipher text policy-attribute-based encryption (CP-ABE) for secure data dispersal among the source to destination with game theory-based jammer attack detection model. The performance of the proposed scheme is assessed with respect to different evaluation metrics in different node density levels. The results obtained clearly describes the proposed scheme provides a flexible and feasible decision to select the route that meets the security requirement of data packets transmission in MANETs environment.